Bismuth germanate coupled to near ultraviolet silicon photomultipliers for time-of-flight PET. (2nd September 2016) - Kwon, Sun Il; Gola, Alberto; Ferri, Alessandro; Piemonte, Claudio; Cherry, Simon R
Abstract: Bismuth germanate (BGO) was a very attractive scintillator in early-generation positron emission tomography (PET) scanners. However, the major disadvantages of BGO are lower light yield and longer rise and decay time compared to currently popular scintillators such as LSO and LYSO. This results in poorer coincidence timing resolution and it has generally been assumed that BGO is not a suitable scintillator for time-of-flight (TOF) PET applications. However, when a 511 keV photon interacts in a scintillator, a number of Cerenkov photons are produced promptly by energetic electrons released by photoelectric or Compton interactions. If these prompt photons can be captured, they could provide a better timing trigger for PET. Since BGO has a high refractive index (increasing the Cerenkov light yield) and excellent optical transparency down to 320 nm (Cerenkov light yield is higher at shorter wavelengths), we hypothesized that the coincidence timing resolution of BGO can be significantly improved by efficient detection of the Cerenkov photons. However, since the number of Cerenkov photons is far less than the number of scintillation photons, and they are more abundant in the UV and blue part of the spectrum, photosensors need to have high UV/blue sensitivity, fast temporal response, and very low noise in order to trigger on the faint Cerenkov signal. In this respect, NUV-HD silicon photomultipliers (SiPMs) (FBK, Trento, Italy) are an excellent fit for our approach. In this study, coincidence events were measured using BGO crystals coupled with NUV-HD SiPMs. The existence and influence of Cerenkov photons on the timing measurements were studied using different configurations to exploit the directionality of the Cerenkov emissions. Coincidence resolving time values (FWHM) of 270 ps from 2 × 3 × 2 mm 3 BGO crystals and 560 ps from 3 × 3 × 20 mm 3 BGO crystals were obtained. To our knowledge, these are the best coincidence resolving time values reported for BGO to date. With these values, BGO can be considered as a relevant scintillator for TOF PET scanners, especially if photodetectors with even better near UV/blue response can be developed to further improve the efficiency of Cerenkov light detection.